2019
DOI: 10.1111/cobi.13326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of publication bias on conservation planning

Abstract: Conservation planners need reliable information on spatial patterns of biodiversity. However, existing data sets are skewed because some ecosystems, taxa, and locations are underrepresented. We determined how many articles have been published in recent decades on the biodiversity of different countries and their constituent provinces. We searched the Web of Science catalogues Science Citation Index (SCI) and Social Science Citation Index (SSCI) for biodiversity‐related articles published from 1993 to 2016 that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 44 publications
3
37
0
1
Order By: Relevance
“…The converse geographical bias toward the United States, Australia, and the United Kingdom is also in alignment with previous structured reviews and maps (Griffiths & Dos Santos 2012;Di Marco et al 2017). For example, Hickisch et al (2019), in the context of conservation planning, found a publication bias against research in central and north Africa and central Asia. Like their results, our results reveal a similar trend and gap.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The converse geographical bias toward the United States, Australia, and the United Kingdom is also in alignment with previous structured reviews and maps (Griffiths & Dos Santos 2012;Di Marco et al 2017). For example, Hickisch et al (2019), in the context of conservation planning, found a publication bias against research in central and north Africa and central Asia. Like their results, our results reveal a similar trend and gap.…”
Section: Discussionsupporting
confidence: 82%
“…Like their results, our results reveal a similar trend and gap. As Hickisch et al (2019) suggests, this finding may stem from persistent armed conflicts. Di Marco et al (2017) suggests a publication filter process is another plausible explanation, wherein research conducted in developing countries is unlikely to be published in leading journals, resulting in the geographic biases.…”
Section: Discussionmentioning
confidence: 95%
“…America broadly corresponds to patterns of publication density in Di Marco et al (2017) and Hickisch et al (2019). We also found that the United Kingdom rivalled the United States of America as a hotspot of evidence for these two taxonomic groups, which did not seem to be as apparent in Wilson et al (2016) or Hickisch et al (2019), but was in Di Marco et al (2017). This hotspot contrasts, particularly for amphibians, with their low species richness in the UK (only seven native amphibian species).…”
Section: Discussionsupporting
confidence: 74%
“…Patterns in research effort are also influenced by the physical accessibility of locations to researchers from the Global North (Reddy and Dávalos 2003) and multiple socio-economic variables (e.g. GDP per capita, affluence, language, security, conflict and infrastructure; Fisher et al 2011, Martin, Blossey, andEllis 2012;Amano and Sutherland 2013;Meyer et al 2016;Hickisch et al 2019). These factors are likely to affect the representation of different biomes or habitats in the evidence base (Fazey et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite world-wide efforts, there are still major areas for which almost no information on biodiversity is available (e.g. Hickisch et al, 2019). But technological advances, in particular camera traps and acoustic recorders, make it possible to obtain a first glimpse on the presence and distribution of larger or highly vocal animals like mammals and birds in relatively short time and with a reasonable budget.…”
Section: Resultsmentioning
confidence: 99%